Myocardial Mass Contributes to the Discrepancy Between Anatomic Stenosis Severity Assessed by Intravascular Ultrasound and Fractional Flow Reserve in Intermediate Lesions of the Coronary Artery. Issue 2 (1st June 2017) - Yoon, Myeong‐Ho; Tahk, Seung‐Jea; Lim, Hong‐Seok; Yang, Hyoung‐Mo; Seo, Kyoung‐Woo; Choi, Byoung‐Joo; Choi, So‐Yeon; Hwang, Gyo‐Seung; Park, Jin‐Sun; Shin, Joon‐Han
Abstract : Objectives: The present study investigated the major contributors to the discrepancy between the minimal lumen area (MLA) and fractional flow reserve (FFR). Background: There was considerable discrepancy between MLA or diameter stenosis (DS) and FFR. Methods: We enrolled 744 patients with intermediate stenoses of the left anterior descending artery (LAD). Summed epicardial coronary artery length distal to the target stenosis was obtained from each longest view of the vessels on the coronary angiograms. Mismatching was defined as a lesion with FFR of >0.80 and MLA smaller than the best cut‐off value (BCV) for predicting FFR of ≤0.80. Reverse mismatching was defined as a lesion with FFR of ≤0.80 and MLA larger than the BCV. Results: Summed epicardial coronary artery length was longer at the lesions of proximal LAD than that of middle LAD (380 mm ± 82 mm vs. 341 mm ± 80 mm, P < 0.001). Reverse mismatching was found more frequently in the proximal than middle LAD (28.3% vs. 5.5%, P < 0.001). Independent predictors of FFR ≤ 0.80 were age, male, multi‐vessel disease, proximal LAD lesion, MLA, DS, plaque burden at distal reference, lesion length and summed epicardial coronary artery length. Proximal LAD lesion was an independent predictor of reverse mismatching (hazard ratio 3.162, 1.858–5.382, P < 0.001). Conclusions: Myocardial mass subtended by a lesion is an important factor predicting FFR ≤0.80 and discrepancy between FFR and MLA. Myocardial mass subtended by a lesion should be considered when determining the revascularization therapy by intravascular ultrasound parameters. © 2017 Wiley Periodicals, Inc.